STRATEGI PENGEMBANGAN BISNIS BADAN USAHA MILIK PETANI (BUMP) PT PADI ENERGI PROKLAMASI DI KABUPATEN KARAWANG, JAWA BARAT - Doni Sahat Tua Manalu (Universitas Garut, 2018)
Currently some areas of Indonesia are being developed Badan Usaha Milik Petani (BUMP) as a form of institutional agribusiness, especially in the central area of rice production. Karawang regency is one of the regions in Indonesia who have great potential in rice production. BUMP PT Padi Energi Proklamasi is one that stands in the Karawang regency, West Java. This research aims to identify environmental external factors into opportunities and threats as well as the company's internal environmental factors that the company's strengths and weaknesses, formulate alternative strategies that the company can run according to environmental conditions and analyze the company's strategic priorities that can be run by enterprises in accordance with the company's environmental conditions. Data analysis was carried out qualitative and quantitative descriptive with EFE matrix-IFE, IE Matrix, SWOT matrix and QSPM. EFE matrix evaluation results in a score of 3.148 indicates that the BUMP PT Padi Energi Proklamasi respond both opportunities and threats that exist in the industry well. Based on the matrix IFE total weighted score is 3.684. The results obtained from processing QSPM priority strategies that can be run by BUMP PT Padi Energi Proklamasi is improving the quality of services to members through the existing facilities and infrastructure as well as government policies and others who support the business with the highest value that is equal to TAS 7.147. Keywords : Strategy, Institutional Agribusiness, BUMP PT Padi Energi Proklamasi